(untitled) (Palíndromo, 2025)
Reino dos bichos e dos animais é o meu nome was originally published in 2001, making know the name of Stella do Patrocínio, author of the falatório (speech) (term of the author herself) that inspired the book. Recorded at Colônia Juliano Moreira – a psychiatric complex where she was interned for decades – excerpts of her speech were transcribed long after her death. The full audio recordings were made available only twenty-one years after the book, thanks to the effort made by Sara Ramos in her dissertation. With the intention of contributing to the discussions that highlight the problematic aspects of the unrestricted celebration of Stella do Patrocínio as a poet, contrasting this with the deprivation of care in freedom and the right to decide for herself that she suffering (related to state policies in the 20th century against Black and diagnosed individuals, and their lasting impacts on health assistance and cultural scenario in Brazil), this letter was sent to the Jabuti Prize, to which the book was nominated in 2002. Addressed along with some pages from the anthology Escritos de Artistas: anos 60/70, in which all the words from one of its chapters were omitted except for a surname, the letter argues for the importance of the negative responses that Stella provided during the recorded conversations, most of which were not transcribed in the book nominated for the prize. Understanding Stella’s refusals, her quest for quietude, as being as important as her falatório.